Acute bronchopulmonary infection due toStreptococcus milleri in a child with cystic fibrosis. Issue 3 (1st March 1999) - Cade, A; Denton, M; Brownlee, K G; Todd, N; Conway, S P
Abstract : An 8 year old girl with cystic fibrosis had severe respiratory disease associated with chronic Pseudomonas aeruginosa bronchopulmonary infection. Despite regular courses of intravenous antipseudomonal antibiotics, she continued to deteriorate over 18 months with persistent productive cough, worsening respiratory function, and increasing oxygen dependence. During her 11th admission Streptococcus milleri was isolated from sputum cultures in addition to P aeruginosa . She failed to respond to antipseudomonal antibiotics but improved dramatically with the addition of intravenous benzylpenicillin. Although S milleri is considered a normal mouth commensal and its isolation from sputum of cystic fibrosis patients is of uncertain significance, it was associated with clinically significant infection in this child. S milleri was eradicated with antibiotic treatment and clinical improvement has been maintained.